Validation of the Committed Action Questionnaire-8 and Its Mediating Role Between Experiential Avoidance and Life Satisfaction Among Chinese University Students - Li, Ya; Yang, Fei-long; Pan, Chen; Chu, Qian-qian; Tang, Qiu-ping (Frontiers in Psychology, 2021)
Background: Committed action is one of the core processes of psychological flexibility derived from Acceptance and Commitment Therapy (ACT). It has not been widely investigated in mainland China as appropriate measures are lacking. The aims of the current study were to validate a Chinese (Mandarin) version of the Committed Action Questionnaire (CAQ-8) in a nonclinical college sample, and to explore whether committed action would have a mediating effect in the association between experiential avoidance (EA) and life satisfaction. Methods: We translated the CAQ-8 into Chinese (Mandarin). A total of 913 Chinese undergraduates completed a set of questionnaires measuring committed action, EA, mindful awareness, anxiety, depression, stress and life satisfaction. For test-retest reliability 167 respondents completed the CAQ-8 again four weeks later. Results: The entire scale of CAQ-8 (Mandarin) and two subscales showed adequate internal consistency, and acceptable test-retest reliability. Confirmatory factor analyses confirmed the two-factor structure and the convergent and criterion validity were acceptable. Committed action was correlated with less experiential avoidance, more mindful awareness, less depressive symptoms, less anxiety, less stress and more life satisfaction. In bootstrap mediation analyses, committed action partially mediated the association between experiential avoidance and life satisfaction. Conclusions: The results suggest that the CAQ-8 (Mandarin) is a brief, psychometrically sound instrument to investigate committed action in Chinese populations, and the relationship between experiential avoidance and life satisfaction was partially explained by committed action. This study provides new information about the usefulness of CAQ-8 in the studied population and a better understanding of how experiential avoidance and committed action interact to affect life satisfaction in an educated nonclinical population.